An Analysis of Moral and Cultural Values in the Story of Atu Belah from Central Aceh - Marlina Marlina; Herlinda Herlinda; Nurmalina Nurmalina; Mukhlis Lbs (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
This story about Atu Belah is one of the most famous stories for Gayo children. Once upon a time, in Penarun Village, Gayo Highlands, Central Aceh, there lived a low-income family. In his free time, his father always hunted deer in the forest. In addition, he also caught many grasshoppers in the fields to eat if he did not manage to find a game. He collected the grasshoppers little by little in the barn. However, he had caused the death of his wife. This study aims to (1) describe the moral values ??in the Atu Belah story and (2) describe the cultural values ??in the Atu Belah story. This research is a qualitative descriptive study. The data source in this study is the story of Atu Split, published on the website of the Central Aceh District Government. The object of this research is the moral and cultural values ??of the Atu Split story. The data collection technique was done by reading and taking notes. The results of this study indicate that (1) the moral values ??contained in the stone split story are (a) the value of hard work, (b) the value of independence, (c) the value of curiosity, and (d) the value of responsibility; (2) the cultural values ??contained in the stone split story are philosophical values, (b) the value of patience, and (c) true values.